Technologies for Beneficial Microorganisms Inocula Used as Biofertilizers - E. Malusá; L. Sas-Paszt; J. Ciesielska (The Scientific World Journal)
The increasing need for environmentaly friendly agricultural practices is driving the use of fertilizers based on beneficial microorganisms. The latter belong to a wide array of genera, classes, and phyla, ranging from bacteria to yeasts and fungi, which can support plant nutrition with different mechanisms. Moreover, studies on the interactions between plant, soil, and the different microorganisms are shedding light on their interrelationships thus providing new possible ways to exploit them for agricultural purposes. However, even though the inoculation of plants with these microorganisms is a well-known practice, the formulation of inocula with a reliable and consistent effect under field conditions is still a bottleneck for their wider use. The choice of the technology for inocula production and of the carrier for the formulation is key to their successful application. This paper focuses on how inoculation issues can be approached to improve the performance of beneficial microorganisms used as a tool for enhancing plant growth and yield.